Infrared Image Enhancement and Segmentation for Extracting the Thermal Anomalies in Electrical Equipment - M. S., Jadin; Soib, Taib (KTU, 2012)
Thermal anomalies in electrical equipments can be extracted if its infrared image is segmented properly. However, segmenting the infrared image is a very challenging task due to blur and low quality of the obtained images. So, it is very important to enhance the image prior to segmentation. This paper proposes an image enhancement method by adjusting the intensity of the image. Firstly, the intensity of the original image is inverted. Then, the warm region is enhanced by subtracting the original image with the inverted image. Experimental results through different segmentation algorithms show that by enhancing the infrared image using the proposed algorithm could improve the segmentation performance. Ill. 4, bibl. 16, tabl. 1 (in English; abstracts in English and Lithuanian).